Pengaruh Celebrity Endorsement dan Brand Image terhadap Purchase Intention dengan Brand Trust sebagai Variabel Mediasi - Rifaldo Hardion; Galuh Mira Saktiana (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2026)
Tujuan penelitian ini adalah untuk menguji pengaruh celebrity endorsement terhadap purchase intentions pada produk sepatu Under Armour. Untuk menguji pengaruh celebrity endorsement terhadap brand trust pada produk sepatu Under Armour. Untuk menguji pengaruh brand image terhadap purchase intention pada produk sepatu Under Armour. Untuk menguji pengaruh brand image terhadap brand trust pada produk sepatu Under Armour. Untuk menguji pengaruh brand trust terhadap purchase intention pada produk sepatu Under Armour. Untuk menguji brand trust dapat memediasi pengaruh celebrity endorsement dan brand image terhadap purchase intention pada produk sepatu Under Armour. Penelitian ini termasuk dalam kategori penelitian kuantitatif. Populasi dari penelitian ini adalah semua pengguna Under Armour di Jabodetabek. Probability sampling dan non-probability sampling adalah dua kategori utama teknik pengambilan sampel. Berdasarkan pada hasil analisis data, dapat ditarik kesimpulan Celebrity endorsement tidak berpengaruh terhadap purchase intention pada produk sepatu brand Under Armour. Celebrity endorsement berpengaruh positif terhadap brand trust pada produk sepatu brand Under Armour. Brand image berpengaruh positif terhadap purchase intention pada produk sepatu brand Under Armour. Brand image berpengaruh positif terhadap brand trust pada produk sepatu brand Under Armour. Brand trust berpengaruh positif terhadap purchase intention pada produk sepatu brand Under Armour. Brand trust dapat memediasi pengaruh celebrity endorsement terhadap purchase intention pada produk sepatu brand Under Armour. Brand trust dapat memediasi pengaruh brand image terhadap purchase intention pada produk sepatu brand Under Armour. The purpose of this study was to examine the effect of celebrity endorsement on purchase intentions for Under Armour shoe products. To examine the effect of celebrity endorsement on brand trust in Under Armour shoe products. To examine the effect of brand image on purchase intention in Under Armour shoe products. To examine the effect of brand image on brand trust in Under Armour shoe products. To examine the effect of brand trust on purchase intention in Under Armour shoe products. To examine the effect of brand trust on purchase intention in Under Armour shoe products. To examine brand trust can mediate the effect of celebrity endorsement on purchase intention in Under Armour shoe products. To examine brand trust can mediate the effect of brand image on purchase intention in Under Armour shoe products. This study is included in the quantitative research category. The population of this study were all Under Armour users in Jabodetabek. Probability sampling and non-probability sampling are two main categories of sampling techniques. Based on the results of data analysis, it can be concluded that celebrity endorsement has no effect on purchase intention in Under Armour brand shoe products. Celebrity endorsement has a positive effect on brand trust in Under Armour brand shoe products. Brand image has a positive effect on purchase intention in Under Armour brand shoe products. Brand image has a positive effect on brand trust in Under Armour brand shoe products. Brand trust has a positive effect on purchase intention in Under Armour brand shoe products. Brand trust can mediate the influence of celebrity endorsement on purchase intention in Under Armour brand shoe products. Brand trust can mediate the influence of brand image on purchase intention in Under Armour brand shoe products.